Klasrum drama mga anyo ng dulaan para sa paaralan - Casanova, Arthur P. (Arthur de la Peña),eauthor (Mandaluyong City Anvil Publishing, Inc., 2011)
Rules and guidelines for developing different genres of theater in the classroom.
Keywords: Tagalog drama -- Study and teaching; Drama in education -- Philippines; Children's theater -- Philippines